The Influence of Service Quality on Loyalty Through Satisfaction at The Elizabeth Store in Palangka Raya - Rita Yuanita Toendan; Noorjaya Nahan (Indonesian Journal of Economic & Management Sciences, 2023)
Research in the field of marketing with the aim of this research is to measure and analyze the influence of service quality on customer loyalty at Elizabeth Store Palangka Raya. Measuring and analyzing the influence of satisfaction on loyalty at Elizabeth Store Palangka Raya. Measuring and analyzing the influence of service quality on satisfaction by analyzing the influence of service quality on loyalty through satisfaction. The population in this study were 150 consumers who shopped at the Elizabeth Store in Palangka Raya City. Primary and secondary data sources, data collection methods using observation, and distributing questionnaires. The analytical tool used in this research is Smart-PLS Version 3.0. The results of this research show that service quality has a positive and significant effect on loyalty. Consumer satisfaction has a positive and significant effect on loyalty. Service quality has a positive and significant effect on satisfaction. Service Quality on loyalty through Satisfaction has a positive and significant effect. The implications of the results show that service quality is important in increasing consumer satisfaction so that they trust the store as shown by loyalty